Organoidi ledvic in njihova uporaba v medicini - Levstek, Tina (Medicinski razgledi, 2022)
When kidney dysfunction progresses to end-stage kidney disease, therapeutic options are very limited. Therefore, understanding the biological processes in the kidneys that lead to the deterioration of kidney function is very important, because it could allow the development of new therapeutic approaches to prevent the development of kidney dysfunction or slow its progression. In the last decade, considerable progress has been made in understanding the cellular biological processes during embryonic kidney development in humans, followed by the development of kidney organoids, which are complex in vitro models. In organoids, cells self-organize into formations with a complex structure that mimics the kidney structure in vivo. Despite the current limitations of kidney organoids, such as lack of vascularity and high variability, the possibilities for their use in medicine are numerous. Kidney organoids already enable the study of kidney development and certain disease processes, nephrotoxicity testing, and drug screening, which increases their potential for use in personalized and regenerative medicine.
Keywords: ledvice; matične celice; organoidi